MAINSTREAMING OF ISLAMIC PHILOSOPHY DEVELOPMENT PATTERNS - Adenan, Adenan (Program Doktor Akidah dan Filsafat Islam, 2025)
There are three patterns of development of mainstreaming Islamic philosophy, namely the First Pattern; Peripatetism (wisdom of masyaiyah) is a serious effort and effort made by Muslim philosophers to combine the philosophical and religious truths of the characters starting from Akindi, Al-Farabi and Ibn Sina. Second Pattern; Illuminationism (wisdom of isyroqiyah) is a serious effort by Muslim philosophers to combine the truth of philosophy and Sufism with its central figure Suhrawardi Al Maqtul. Third Pattern; Transcendentalism (wisdom of muta'aliyah) is a serious effort and effort made by Muslim philosophers to combine the truth of Philosophy, Kalam and Sufism with the character Mulla Sadra. These three features have provided a valuable legacy for the discipline of Islamic philosophy.